SHMT inhibition is effective and synergizes with methotrexate in T-cell acute lymphoblastic leukemia - García-Cañaveras, Juan C. (Leukemia, 2020)
Folate metabolism enables cell growth by providing one-carbon (1C) units for nucleotide biosynthesis. The 1C units are carried by tetrahydrofolate (THF), whose production by the enzyme DHFR is targeted by the important anticancer drug methotrexate. 1C units come largely from serine catabolism by the enzyme SHMT, whose mitochondrial isoform is strongly upregulated in cancer. Here we report the SHMT inhibitor SHIN2 and demonstrate its in vivo target engagement with (13)C-serine tracing. As methotrexate is standard treatment for T-cell acute lymphoblastic leukemia (T-ALL), we explored the utility of SHIN2 in this disease. SHIN2 increases survival in NOTCH1-driven mouse primary T-ALL in vivo. Low dose methotrexate sensitizes Molt4 human T-ALL cells to SHIN2, and cells rendered methotrexate resistant in vitro show enhanced sensitivity to SHIN2. Finally, SHIN2 and methotrexate synergize in mouse primary T-ALL and in a human patient-derived xenograft in vivo, increasing survival. Thus, SHMT inhibition offers a complementary strategy in the treatment of T-ALL.